The Effect of Documenting Patient Weight in Kilograms on Pediatric Medication Dosing Errors in Emergency Medical Services. (17th February 2023) - Ward, Caleb E.; Taylor, Michael; Keeney, Clare; Dorosz, Emily; Wright-Johnson, Cynthia; Anders, Jennifer; Brown, Kathleen
Abstract: Objectives: Up to 40% of children who receive a medication from emergency medical services (EMS) are subject to a dosing error. One of the reasons for this is difficulties adjusting dosages for weight. Converting weights from pounds to kilograms complicates this further. This is the rationale for the National EMS Quality Alliance measure Pediatrics-03b, which measures the proportion of children with a weight documented in kilograms. However, there is little evidence that this practice is associated with lower rates of dosing errors. Therefore, our objective was to determine whether EMS documentation of weight in kilograms was associated with a lower rate of pediatric medication dosing errors. Methods: We conducted a retrospective cross-sectional study of children 0-14 y/o in the 2016-17 electronic Maryland Emergency Medical Services Data System that received a weight-based medication. Using validated age-based formulas, we assigned a weight to patients without one documented. Doses were classified as errors and severe errors if they deviated from the state protocol by >20% or >50%, respectively. We compared the dosage errors in the two groups and completed secondary analyses for specific medications and age groups. Results: We identified 3, 618 cases of medication administration, 53% of which had a documented weight. Patients with a documented weight had a significantly lower overall dose error rate than those without (22 vs. 26%, p <.05). A sensitivity analysis in which we assigned a weight to those patients with a weight recorded did not significantly change this result. Sub-analyses by individual medication showed that only epinephrine (34 vs. 56%, p <.05) and fentanyl (10 vs. 31%, p <.05) had significantly lower dosing error rates for patients with a documented weight. Infants were the only age group where documenting a weight was associated with a lower dosing error rate (33 vs. 53% p <.05). Conclusion: Our findings suggest that documenting a weight in kilograms is associated with a small but significantly lower rate of pediatric dosing errors by EMS. Documenting a weight in kilograms appears particularly important for specific medications and patient age groups. Additional strategies (including age-based standardized dosing) may be needed to further reduce pediatric dosing errors by EMS.